2020
DOI: 10.2147/rmhp.s277917
|View full text |Cite
|
Sign up to set email alerts
|

<p>Does Performing the Chinese Eye Exercises Help Protect Children’s Vision? – New Evidence from Primary Schools in Rural Northwestern China</p>

Abstract: Background: The high prevalence of myopia among school-age children in China has raised serious concerns about protecting Chinese students' vision. While the regular performance of the Chinese eye exercises has been adopted as a preventive approach in China since the mid-1960s, these exercises' effectiveness at protecting students' vision has remained largely unknown. This study attempts to provide new evidence of the impact of regularly performing the exercises on Chinese students' visual outcomes, based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Studies have shown that, compared with people who do not perform eye exercises regularly, people who perform eye exercises regularly have a 6.2% increase in the probability of vision damage and a 7.6% increase in the probability of myopia. Assuming that Chinese eye exercises are effective in protecting children's vision when used correctly (or at least do not pose a significant threat to children's visual health), we found that adverse effects may be caused by students performing eye exercises incorrectly (19). In addition, existing studies have proved that careful practice of correct eye exercises can make students take the initiative to rest the tired muscles with regular acupuncture points around their eyes (18,37).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Studies have shown that, compared with people who do not perform eye exercises regularly, people who perform eye exercises regularly have a 6.2% increase in the probability of vision damage and a 7.6% increase in the probability of myopia. Assuming that Chinese eye exercises are effective in protecting children's vision when used correctly (or at least do not pose a significant threat to children's visual health), we found that adverse effects may be caused by students performing eye exercises incorrectly (19). In addition, existing studies have proved that careful practice of correct eye exercises can make students take the initiative to rest the tired muscles with regular acupuncture points around their eyes (18,37).…”
Section: Discussionmentioning
confidence: 83%
“…The use of an instrumental variable method and bivariate probability method revealed the adverse effects of regular Chinese eye exercises on students' vision. Students who exercised regularly were 6.2 percentage points more likely to have vision impairment and 7.6% points more likely to be nearsighted than students who did not exercise regularly (19). The two cohort studies were followed at 9 months, 21 months, and 3 years.…”
Section: Correlation Estimates From Other Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether these exercises could make a difference remains unclear. A cross-sectional survey by Huang et al did not indicate the link between Chinese eye exercises and myopia [ 40 ]. Furthermore, the relationship between education and myopia has always been a hot topic.…”
Section: Discussionmentioning
confidence: 99%
“…Together with these related findings, our finding of a robust association between myopia and depression also highlights the importance of formulating policies and measures to help reduce myopia prevalence among school-age children. The studies by Li et al (2022) [ 7 ] and Huang et al (2020) [ 46 ] provide recent examples.…”
Section: Discussionmentioning
confidence: 99%